KEBIJAKAN HARGA BERAS DITINJAU DARI DIMENSI PENENTU HARGA (Forum Penelitian Agro Ekonomi, 2017)
Rice is a staple food for most of Indonesian and becoming a quasi-public commodity. The government of Indonesia is implementing rice price policies in achieving domestic rice price stability. Floor price policy aims at protecting farm-gate price, while ceiling price aims at protecting price at consumers’ level. This paper aims to discuss a conceptual review of rice price policies. The current rice price policies lead to policies that take into account some dimensions of the determining factors, namely the dimensions of products, varieties, qualities, and levels in marketing chain. Existing rice price policies were governed by the segmented regulations. A comprehensive rice price policy is required to improve effectiveness and efficiency of the policies. It is necessary to formulate a policy capable of harmonizing the relationship between producer farmers, processing industries, marketing institutions, and consumers in a supply chain system.
Keywords: pricing policy; price stabilization; floor price; ceiling price; rice price